Metazoan Parasite Life Cycles: Significance for Fish Mariculture. Issue 12 (December 2020) - Huston, Daniel C.; Ogawa, Kazuo; Shirakashi, Sho; Nowak, Barbara F.
Abstract : Marine fish are a nutritious and high-value food commodity, but many wild-capture fisheries are in decline. Thus, marine fish culture is expected to expand greatly in coming years. Management of disease is a major problem in this industry, and metazoan parasites are among the most significant disease agents in terms of economic loss and animal welfare. Current methods for controlling metazoan parasites are mostly reactionary and rely on chemical treatment. Such methods are ultimately unsustainable. Here, we summarise the life cycles of marine metazoan parasites and how this knowledge can be used for nonchemical management and control. To aid the sustainable growth of marine fish culture, we advocate for a renewed research focus on the basic life history characteristics of parasites. Highlights: Management of diseases comprises a significant part of operating costs in fish mariculture, and metazoan parasites are among the most problematic. Metazoan parasites have become a significant animal welfare concern in mariculture while the chemical control methods employed for parasites are coming under increased environmental scrutiny and government regulation. More holistic management methods are needed for the future sustainability of fish mariculture, and the exploitation of parasite life cycles for control seems especially promising. Life cycles have been elucidated for few known parasites, and knowledge of marine parasite life cycles lags far behind those from freshwater ecosystems. There is an urgent need for research elucidating basic life history characteristics of marine parasites as new diseases are likely to emerge as mariculture expands.